The Landscape of Severe Combined Immunodeficiency Newborn Screening in the United States in 2020: A Review of Screening Methodologies and Targets, Communication Pathways, and Long-Term Follow-Up Practices - Sheller, Ruthanne; Ojodu, Jelili; Griffin, Emma; Edelman, Sari; Yusuf, Careema; Pigg, Trey; Huston, Alissa; Fitzek, Brian; Boyle, John G.; Singh, Sikha (Frontiers in Immunology, 2020)
Severe combined immunodeficiency (SCID) are T cell development disorders in the immune system and can be detected at birth. As of December 2018, all 53 newborn screening programs within the United States and associated territories offer universal screening for SCID. The Association of Public Health Laboratories (APHL), along with the Immune Deficiency Foundation (IDF), surveyed public health newborn screening system laboratory and follow-up coordinators regarding their newborn screening program’s screening methodologies and targets, protocols for stakeholder notifications, and long-term follow-up practices. This report explores the variation that exists across newborn screening practices, revealing needs for efficiencies and educational resources across the newborn screening system to ensure the best outcomes for newborns.